Is Early Flare After Extracorporeal Shock Wave Therapy a Marker of Favorable Clinical Response in Plantar Fasciitis: A Retrospective Cohort Study - Zehra Duman Şahin; Selkin Yılmaz Muluk; Vedat Altuntaş; Evin Aslan; Şevval Dirican; Sevcan Uğur (Ahi Evran Medical Journal, 2026)
Purpose: This study aimed to investigate whether an early pain flare following extracorporeal shock wave therapy (ESWT) serves as a marker for favorable short-term clinical outcomes in patients with plantar fasciitis (PF) and to examine the association between calcaneal spur characteristics and flare occurrence.Materials and Methods: This retrospective observational cohort study included 69 adults (aged 18–65) diagnosed with PF at a tertiary center between April and October 2025. All patients completed a standardized ESWT protocol consisting of three weekly sessions (12 Hz, 3.0 bar, 2000 shocks/session) without local anesthesia. Patients were categorized as flare-positive if they experienced a transient increase in heel pain within 72 hours post-treatment. Pain and function were assessed using the Visual Analog Scale (VAS) and Foot Function Index (FFI) at baseline and end of treatment. Statistical analyses included paired t-tests, Wilcoxon signed-rank tests, independent samples t-tests, and ANCOVA models to adjust for baseline imbalances.Results: An early flare occurred in 26 patients (37.7%), typically within hours of treatment. Both groups showed significant improvements in VAS and FFI scores (p<0.05). However, there were no significant differences between groups in absolute change scores for pain or function. After adjusting for baseline scores, flare status was not independently associated with pain reduction (p=0.701) or functional recovery (p=0.435). Calcaneal spur presence and length were not associated with flare occurrence.Conclusion: Early pain flare is a common, self-limited reaction following ESWT but does not predict superior short-term clinical response in plantar fasciitis.